Estándares de desempeño docente - Oña Oña, Liliana Marilú (2017)
Educationorn is priority in the social scene of the peoples, that should be understood from various perspectives, even from the everyday experiences of the children and teenagers, thus the research detailed a general diagnostics on the '' teachers´ standard performance at Unidad Educativa ''Vicente Leon'' whose objective research was: to determine the standards of teachers´ development in the field of curriculum development, as it has been observed a deficit in the fulfillment of them; therefore, affects the quality in education at school. This research was developed under the socio-educational, with quali-quantitative approach, bibliographical documentary and field. analytical and syntactical methods were applied, they helped strengthen and execution of the research; after applying surveys to students and teachers, it was concluded that " standards of teachers´….